(untitled) (Research, Society and Development, 2021)
Objective: This study aims to outline the epidemiological profile of patients seen in the physiotherapy sector of a teaching clinic in the interior of Ceará. Methods: this is a cross-sectional, quantitative, and retrospective study. For this, all medical records of patients treated in the physiotherapy sector of the school-clinic during 2019 were analyzed. The variables analyzed were gender, age group, race, profession, clinical diagnosis, main complaint, affected segments, kinesiological diagnosis functional (CIF) and physiotherapeutic treatment. Results: there was a prevalence of female individuals (62.80%), aged 60 years or older (31%), of mixed race (43.40%) and working as a homemaker (15%). The most common clinical diagnosis was arthrosis (8%), with main complaint of pain (85.80%) and the most affected segment was the lumbar spine (32.70%). 94.70% received physical therapy care and 83.30% had ICF. Conclusion: knowledge of the epidemiological profile allows physical therapists to recognize the main problems that affect the population, making them more prepared to act both in prevention and treatment, thus providing a better quality of life for these users.